3D geometric morphometric analysis of variation in the human lumbar spine. Issue 3 (15th August 2019) - Lois Zlolniski, Stephanie; Torres‐Tamayo, Nicole; García‐Martínez, Daniel; Blanco‐Pérez, Esther; Mata‐Escolano, Federico; Barash, Alon; Nalla, Shahed; Martelli, Sandra; Sanchis‐Gimeno, Juan A.; Bastir, Markus
Abstract: Objectives: The shape of the human lumbar spine is considered to be a consequence of erect posture. In addition, several other factors such as sexual dimorphism and variation in genetic backgrounds also influence lumbar vertebral morphology. Here we use 3D geometric morphometrics (GM) to analyze the 3D morphology of the lumbar spine in different human populations, exploring those potential causes of variation. Material and methods: We collected 390 (semi) landmarks from 3D models of the CT scans of lumbar spines of seven males and nine females from a Mediterranean population (Spain, Israel) and seven males and either females from a South African population for geometric morphometric (GM) analysis. We carried out Generalized Procrustes Analysis, Principal Components, and Regression analyses to evaluate shape variation; and complemented these analyses with the Cobb Method. Results: The Mediterranean sample was considerably more lordotic than the South African sample. In both populations, female lumbar spines showed proportionally narrower and more craniocaudally elongated lumbar segments than in males. In addition, the point of maximum curvature in females tended to be located more inferiorly than in males. Discussion: Our results show that sexual dimorphism is an important factor of lumbar spine variation that mainly affects features of lumbar spine robustness (height proportions) and the structure—but not the degree—of its curvature. Differences in lordosis, however, are clearer at the inter‐population level. This reflects previous conflicting studies casting doubts on pregnancy as an adaptive factor influencing lordosis. Other factors, for example, shape of the individual lumbar vertebrae and intervertebral discs and their relative proportions within the lumbar spine should be considered when exploring variation in vertebral column morphology.